Traxoprodil atenua as convulsões induzidas por pentilenotetrazol - Martignoni, Felipe Villa (2010)
There is evidence that while polyamines facilitate seizures by positively modulating N-methyl-D-aspartate receptors (NMDAr), selective antagonists of the NR2B-subunit decrease seizures. However, it remains undetermined whether traxoprodil (CP-101,606), an ifenprodil analog that acts as a selective antagonist of the NR2B subunit of the NMDAr, decreases seizure activity. In the current study we investigated whether traxoprodil alters PTZ-induced seizures in adult male Wistar rats by behavioral and electroencephalographical methods. Spermidine (SPD) (2 nmol/site; i.c.v.) facilitated behavioral and electroencephalographical seizures induced by a normally subeffective dose of PTZ (35 mg/kg; i.p.), but did not alter seizure activity induced by convulsant dose of PTZ (70 mg/kg; i.p). Traxoprodil (20 nmol i.c.v.) increased the latency to generalized tonic clonic seizures induced by PTZ (70 mg/kg; i.p). The oral administration of traxoprodil (60 mg/kg) increased the latency to clonic and tonic-clonic seizures, and decreased total time spent in seizures. These data constitute pharmacological evidence supporting a role for NR2B subunit in PTZ-induced seizures. While more studies are necessary to determine whether traxoprodil is a useful anticonvulsant in clinical settings, NR2B subunits may represent new targets of drug development for convulsive disorders.